Hybrid optimal cluster routing protocol for mobile ad hoc network - NIU Xiao-guang1; CUI Li2; HUANG Chang-cheng2 (Tongxin xuebao)
Based on the analysis of the cluster stability and maintaining overhead of cluster routing protocols in mobile ad hoc networks,a optimized clustering strategy was designed and a corresponding optimal cluster based hybrid routing protocol was proposed namely HOCR（hybrid optimal cluster routing）.Simulation results show that HOCR conduces to better scalability,robustness,lower network maintaining overhead and adapts to large scale mobile ad hoc networks.